A Programmable Reference-Voltage Source - Muhammad Taher Abuelma'atti; Sa'ad Muhammad Al-Shahrani (Active and Passive Electronic Components)
A simple circuit for realizing a current(voltage)-controlled reference voltage is presented. The feasibility of obtaining a temperature-insensitive reference voltage is explored. SPICE simulation results are included.